Petrus Hispanus' attributed works: searching for new interpretations - Meirinhos, José (2018)
Brief introduction to the project on Petrus Hispanus and the papers presented at the Symposiumthat was part of SOFIMEs Congress De relatione. It includes a sketch of thecorpus petrinicum and a presentation of some literary, philosophical and doctrinal problemsinvolved, with a consecutive bibliography of the published works and key studies.